(untitled) (Medico Legal Update, 2020)
Background: HIV that cause of AIDS worldwide distributed and the CD4 positive T cells consider chief target cells of HIV. Elimination of HIV is the final goal of HIV treatment, but is rarely achieved. Objective: As CD4T cells count using flow cytometry recently available, we investigated whether CD4T cells count can substitute for HIV plasma viral load RNA quantification in treatment monitoring through comparison the change in CD4 positive T cells count in patients with HIV previous to & afterward initiating ?highly/active/antiviral/therapy ??HAART? & correlation of CD4 T cellscounts with viral load prior to and after initiating HAART in HIV Iraqi patients. Method: Within this study, 25 HIV patients were prospectively analyzed. Patients have been treated with Bilateral/Didanosine, combination (Efavirenz, Emtricitabine, and Tenofovir Disoproxil Fumarate), in addition to Quadruple combination (Elvitegravir,cobicistat,emtricitabine,tenofovir alafenamide (TAF). Quantitative CD4T cells countwere determined with flowcytometry. HIV plasma viral load RNA were determined with RT-PCR at given time points. Results: We find weak negativenon-significant? correlation?(R?-0.267, p? 0. 197 & R?-0.161, p?0. 441) among CD4positive T cellscounts & ?plasma viral load of HIV RNA?in both treated and untreated patients respectively. More importantly, there was significant concordance between an increase or decrease of CD4T cells counts with HIV RNA plasma viral load prior and after initiating of treatment. However, the curve and increase of CD4T cells count enabled prediction of eventual of viral clearance. Conclusions: Quantitative CD4T cells count cannot substitute for HIV RNA plasma viral load quantification during assessment of antiviral therapy: However, the increase of CD4 T cells count does predict eventual HIV RNA plasma clearance. A 2 log 10 increase to above 200 IU/ml is associated with a high likelihood of HIV plasma RNA clearance.